2022
DOI: 10.1093/jpe/rtac009
|View full text |Cite
|
Sign up to set email alerts
|

Warming and grazing enhance litter decomposition and nutrient release independent of litter quality in an alpine meadow

Abstract: Aims Warming and grazing and the changes in litter quality induced by them co-determine litter decomposition and nutrient releases in grazing ecosystems. However, their effects have previously been studied in isolation. Methods We conducted a two factorial experiment with asymmetric warming using infrared heaters and moderate grazing in an alpine meadow. Litter samples were collected from all plots in each treatment, among wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…In the northern region of China, MAT showed an increasing trend, resulting in a net decrease in SOCD in the region ( Table 3 ; Figure 6B ). This is due to the fact that (i) the fine and coarse root mass quantity and quality reduced with increased temperature, and the decline in root mass was an important cause of the loss in soil organic matter ( Rasse et al., 2005 ; Ofiti et al., 2021 ), and (ii) the temperature rise would accelerate the decomposition of soil organic matter and thus reduce SOCD ( Duan et al., 2013 ; Lv et al., 2020 ; Li B et al., 2022 ). However, in the southern, northwestern, and Qinghai–Tibetan regions, the climate warming seemed to increase SOCD ( Table 3 ; Figures 6A, C, D ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the northern region of China, MAT showed an increasing trend, resulting in a net decrease in SOCD in the region ( Table 3 ; Figure 6B ). This is due to the fact that (i) the fine and coarse root mass quantity and quality reduced with increased temperature, and the decline in root mass was an important cause of the loss in soil organic matter ( Rasse et al., 2005 ; Ofiti et al., 2021 ), and (ii) the temperature rise would accelerate the decomposition of soil organic matter and thus reduce SOCD ( Duan et al., 2013 ; Lv et al., 2020 ; Li B et al., 2022 ). However, in the southern, northwestern, and Qinghai–Tibetan regions, the climate warming seemed to increase SOCD ( Table 3 ; Figures 6A, C, D ).…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that wind speed, sunshine duration, and humidity also affect SOCD ( Lu et al., 2013 ; Lei et al., 2019 ; Huang et al., 2022 ). As an important anthropogenic factor, grazing and its intensity (standard sheep unit ha −1 year −1 ) can disturb the carbon balance in ecosystems by affecting SOCD ( Zhang et al., 2016 ; Zhou G et al., 2017 ; Li B et al., 2022 ). For example, slight and heavy grazing intensity may result in SOC loss, while moderate grazing intensity probably promoted SOC accumulation ( Jiang et al., 2020 ; Zhang M et al., 2018 ; Xie and Wu, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The study area, located on the Qinghai-Tibet Plateau, experiences temperature-driven effects on the soil organic carbon cycle in meadow grassland and swamp ecosystems. Global warming is leading to permafrost melting, accelerating plant root production and turnover rates [43], the decomposition of fallen leaves [44,45], and changes in microbial community structure [46], resulting in increased CO 2 release. As atmospheric CO 2 concentration rises, plants' photosynthesis and productivity increase, leading to greater input of carbon into soil carbon pools [47].…”
Section: Carbon Storage Assessmentmentioning
confidence: 99%